NACore Amyloid Formation in the Presence of Phospholipids - Pallbo, Jon; Imai, Masayuki; Gentile, Luigi; Takata, Shin-ichi; Olsson, Ulf; Sparr, Emma (Frontiers in Physiology, 2020)
Amyloids are implicated in many diseases, and disruption of lipid membrane structures is considered as one possible mechanism of pathology. In this paper we investigate interactions between an aggregating peptide and phospholipid membranes, focusing on the nanometer-scale structures of the aggregates formed, as well as on the effect on the aggregation process. As a model system, we use the small amyloid-forming peptide named NACore, which is a fragment of the central region of the protein α-synuclein that is associated with Parkinson’s disease. We find that phospholipid vesicles readily associate with the amyloid fibril network in the form of highly distorted and trapped vesicles that also may wet the surface of the fibrils. This effect is most pronounced for model lipid systems containing only zwitterionic lipids. Fibrillation is found to be retarded by the presence of the vesicles. At the resolution of our measurements, which are based mainly on cryogenic transmission electron microscopy (cryo-TEM), X-ray scattering, and circular dichroism (CD) spectroscopy, we find that the resulting aggregates can be well fitted as linear combinations of peptide fibrils and phospholipid bilayers. There are no detectable effects on the cross-β packing of the peptide molecules in the fibrils, or on the thickness of the phospholipid bilayers. This suggests that while the peptide fibrils and lipid bilayers readily co-assemble on large length-scales, most of them still retain their separate structural identities on molecular length-scales. Comparison between this relatively simple model system and other amyloid systems might help distinguish aspects of amyloid-lipid interactions that are generic from aspects that are more protein specific. Finally, we briefly consider possible implications of the obtained results for in-vivo amyloid toxicity.